Wheat breeding for tolerance to drought stress at the Cereal Research Non-Profit Company - Cseuz, László (Acta Biologica Szegediensis, 2002)
As selection methods for drought tolerance of wheat, water retention ability, chemical desiccation tests, determination of water relation parameters and carbohydrate accumulation were applied in the breeding system from the start of the breeding among the crossing partners until the last steps on the advanced lines before entering them in official yield performance trials.